The Effect of Applying the Whole Brain Teaching (WBT) Learning Model on Student Learning Outcomes in Social Science Subjects (IPS) Class IV MIN Lubuk Buaya Padang - Rizki Mulyani, Sitti; Mahaputra, M. Rizky (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
This study aims to determine whether the Whole Brain Teaching model influences the social science learning outcomes of fourth grade students at MIN Lubuk Buaya Padang. This research is in the form of quantitative research using a quasy experiment approach. The research population of grade IV students at MIN Lubuk Buaya totaled 78 people and the sampling technique was purposive sampling. Data collection techniques used tests, and test sheet data collection tools. The type of data is in the form of student learning outcomes. The data was processed using a difference test (t-test) and the results obtained were that the average value of the experimental group was higher than the average value of the control class.